PP-042 Masterly formula effectiveness of diazoxide suspension with sorbitol in a neonatal patient. (14th February 2016) - Cañizares, S; Luque, J Cotrina; Fernandez, D; Nieto, P; Alferez, I; Cuadrado, E
Abstract : Background: Congenital hyperinsulinism (HIC) constitutes the more frequent cause of recidivate hypoglycaemia in neonates and lactates. Dose administration of 15 mg/kg/day is the cornerstone of HIC medical treatment. Purpose: To evaluate tolerance, effectiveness and security in a masterly formula of diazoxide 5 mg/mL with sorbitol in a patient with suspicion of congenital HIC. Material and methods: Diazoxide is an active principle with very poor water solubility, which must be mixed with ethanol and glycerol in order that it can be administered as a masterly formula. There are various formulations for the neonatal patient with congenital HIC of diazoxide suspension 5 mg/mL with sorbitol in different concentrations. Because a limit on the concentration for sorbitol does not exist, a bibliographic search on Medline was performed, combining the terms 'excipients' and 'infants'. It was found that the level of sorbitol concentration to which neonates were exposed fluctuated between 0.1 and 2 g/kg/week; the upper limit is where the appearance of gastrointestinal disorders begins. 4 weekly solutions were produced with 0.5, 1, 1.5 and 2 g/kg of sorbitol. Prospective monitoring of the patient was carred out for 9 months to evaluate tolerance and effectiveness of the formula using glycaemia analytics. Results: The newborn presents with hypoglycaemia, the patient begins vomiting and has glucoscaemia of 56 mg/dL. Metabolic study shows a high glucose/insulin ratio. With a concentration of 0.5 g/kg of sorbitol the patient presented nausea and controlled glycaemia (85.105). Weight 3.6 kg. With a solution of 1 g/kg of sorbitol the patient did not present any nausea, with some glycaemia controls >90 mg/dL. Weight 3.6 kg. With a solution of 1.5 g/kg of sorbitol, the patient did not present any nausea. Glycaemia controls was >90 mg/dl. Weight 4.4 kg. With a solution of 2 g/kg of sorbitol, the patient did not present any nausea. Glycaemia was maintained controlled, in every situation, >90 mg/dl. Weight 5.2 kg. Conclusion: Thanks to sorbitol, tolerance was improved without any episodes of nausea and vomiting. Masterly formula of diazoxide in oral suspension helped to resolve HIC in the neonate in a safe and effective way. References and/or Acknowledgements: We thank Torrecardenas Hospital No conflict of interest.